2004
DOI: 10.1080/10915810490436351
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Two-Generation Reproductive Toxicity Study of Methyl Isobutyl Ketone in Rats

Abstract: To evaluate whether methyl isobutyl ketone (MIBK) affects reproductive performance, a two-generation reproduction study was conducted. MIBK was administered to 30 Sprague-Dawley rats/sex/group via whole-body inhalation at concentrations of 0, 500, 1000, or 2000 ppm, 6 h daily, for 70 days prior to mating. F(0) and F(1) females were exposed from mating through gestation day 20 and from postnatal day 5; F(2) litters were maintained through postnatal day 21. No treatment-related mortality of adult animals occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The spectrum of kidney lesions described in the literature after short-term exposures to MIBK (Phillips, et al, 1987;Nemec, et al, 2004) supports the observation that the kidney is the primary target in rats. In the 3-month study of MIBK (Phillips, et al 1987), there were doserelated increases in the severity of hyaline droplet formation and regeneration of PCT cells in male rats, although the highest dose tested in the 13-week study was 1,000 ppm.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The spectrum of kidney lesions described in the literature after short-term exposures to MIBK (Phillips, et al, 1987;Nemec, et al, 2004) supports the observation that the kidney is the primary target in rats. In the 3-month study of MIBK (Phillips, et al 1987), there were doserelated increases in the severity of hyaline droplet formation and regeneration of PCT cells in male rats, although the highest dose tested in the 13-week study was 1,000 ppm.…”
Section: Discussionsupporting
confidence: 79%
“…There was also a positive trend for increases in benign or malignant pheochromocytomas (combined); however increases were neither statistically significant nor exceeded the historical control range. Nemec et al (2004) reported significant changes in adrenal gland weights of female Sprague-Dawley rats exposed to 2,000 ppm MIBK for 70 days, which were the F0 generation of a two generation reproductive study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spermatogenic endpoints were evaluated using the methods described by Nemec et al (2004). Immediately after euthanasia the right epididymis of each F 0 and F 1 male was exposed, excised, and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…Spermatogenic endpoints were evaluated using the methods described by Nemec et al (2004). Immediately upon euthanasia, the right epididymis of each F 0 and F 1 male was exposed, excised, and weighed.…”
Section: Methodsmentioning
confidence: 99%